Multi-disciplinary surgical approach to the management of patients with renal cell carcinoma with venous tumor thrombus: 15 year experience and lessons learned. Issue 1 (December 2016) - Gayed, Bishoy; Youssef, Ramy; Darwish, Oussama; Kapur, Payal; Bagrodia, Aditya; Brugarolas, James; Raj, Ganesh; DiMaio, J.; Sagalowsky, Arthur; Margulis, Vitaly
Abstract Background The management of patients with renal cell carcinoma (RCC) with venous tumor thrombus (VTT) is challenging. We report our 15 year experience in the management of patients with RCC with VTT utilizing a multidisciplinary team approach, highlighting improved total and specifically Clavien III-V complication rates. Methods We reviewed the records of 146 consecutive patients who underwent radical nephrectomy with venous thrombectomy between 1998 and 2012. Data on patient history, staging, surgical techniques, morbidity, and survival were analyzed. Additionally, complication rates between two surgical eras, 1998–2006 and 2006–2012, were assessed. Results The study included 146 patients, 97 males (66 %), and a median age of 61 years (range, 24–83). Overall complications rate was 53 %, high grade complications (Clavien III -V) occurred in 10 % of patients. Most importantly, there was a lower incidence of overall and high grade complications (45 % and 8 %, respectively) in the last 6 years compared to the earlier surgeries included in the study (67 % and 13 % respectively) [p  = .008 and .03, respectively). 30 day postoperative mortality was 2.7 %. 5 year overall survival (5Y- OS) and 5 year cancer specific survival (5Y- CSS) were 51 % and 40 %, respectively. Metastasis was the only independent predictor factor for CSS (HR 3.8, CI 1.9-7.6 andp  < .001) and OS (HR 2.6, CI 1.5-4.7 andp  = .001) in all patients. Conclusions Our data suggest that patients with RCC and VTT can be treated safely utilizing a multidisciplinary team approach leading to a decrease in complication rates.